Analysis of Abundance, Length-Weight Relationship, and Condition Factors of Bulleye Snails (Turbo argyrostoma) on the Batam Coast - Hasibuan, Nirma Adeseprianah; Novianti, Devi; Ramses, Ramses; Amelia, Fitrah; Ismarti, Ismarti (BIOEDUSCIENCE, 2025)
Background: The oxeye snail (Turbo argyrostoma) is a marine gastropod commonly harvested by coastal communities for consumption. Intensive and unregulated harvesting may lead to population decline, raising concerns for ecosystem stability and resource sustainability. This activity directly reduces the population of T. argyrostoma in coastal waters. This study aims to determine the abundance and the correlation between the length-weight and condition factors of T. argyrostoma in the waters of Batam, Riau Islands. Method: This study was performed from September to October 2024. Sampling was conducted at three locations: Kajang Island, Piring Island, and Layang Island. The sampling method conducted was purposive sampling. Water quality measurements were carried out in situ. Abundance was determined based on the number of individuals per unit area. Morphometric data were collected by measuring the body dimensions of T. argyrostoma using digital callipers. Next, the length-weight relationship was analysed using linear regression to determine growth patterns. Results: The aquatic environment met the quality standards set by the Minister of Environment, as outlined in Decree No. 51/2004. The highest abundance of T. argyrostoma was observed at Kajang Island (1.37 ind/m²). Morphometric measurements showed mean shell length (SL) of 39 ± 4.83 mm, weight (W) of 21.3 ± 4.58 g, and shell width (SW) of 30.3 ± 3.25 mm in Layang Island samples. A positive length–weight relationship was identified at all stations (r = 0.73, 0.45, 0.78) with allometric growth coefficient (b) values indicating growth patterns. Condition factors (K and Wr) varied across locations: 6.766 and 70.340 at Piring Island; 6.518 and 103.984 at Kajang Island; and 6.229 and 101.037 at Layang Island, respectively. Conclusion: A positive length–weight relationship was observed at all sites, and variation in condition factors suggests differing ecological pressures. The low Wr value at Piring Island may indicate environmental stress or higher predation pressure.